Men and Women Choose Different Careers in Medicine: Causes and Consequences - Ferrier, Barbara M. (1989)
Women medical graduates of McMaster University were divided into two groups: those in the fields traditionally chosen by women (primary care, general internal medicine, pediatrics, psychiatry, and anesthesia), and those in nontraditional fields (surgery, subspecialties of medicine, and academic medicine). The careers of the two groups of women were then compared with matched groups of men physicians. More women choosing traditional careers worked in another field, frequently health-related, before deciding to enter medicine than women entering nontraditional careers. Fewer of the former had a university education in the natural sciences, and more of them were married at the start of post-graduate training. Both groups of women worked shorter hours than the comparison groups of men. More women in traditional careers had selected group practice than had the corresponding men. Influences on career choices showed more sex similarities than career-type similarities, with women influenced more by factors related to family responsibilities. Few in any group reported that their choices are not their preferences. The results suggest that complete convergence of the medical careers of men and women in the near future is unlikely.